Estimasi Nilai Ekonomi Air dan Eksternalitas Lingkungan Pada Penerapan Irigasi Tetes dan Alur di Lahan Kering Desa Pejarakan Bali - Marpaung, Ridwan (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2013)
Lower appreciation for economic value of irrigation water causes the over pumping on ground water resources in application of drip irrigation system in Pejarakan dry land. It has considerable impacts in term of excessive water use and environmental degradation near the well, while the cost for expenditure to install the drip system is relative expensive .Ground water reserve for drip irrigation in Pejarakan dry land area is very limited so, over pumping for rising crop productions and also for balance cost recovery make negative impact to environment. This study aims to determine the economic value of irrigation water and its environmental externality impact by using depth interview data of dry land farmer at Pejarakan Village. Using Imputation Residual Approach (IRA) on drip irrigation, the water price is Rp.2.008/m3/ha for gasoline pumping energy and Rp.3.836/m3/ha for electrical pumping energy. On the other hand, using furrow irrigation, the water price is zero. Water productivity of drip irrigation is 0,758 kg/m3 (Rp.6.822/m3), higher than the productivity using furrow irrigation that is 0,335 kg/m3 (Rp.3.015/m3). These results also show the efficiency of drip irrigation is 58,1% higher than that of furrow. By taking environmental externality cost into account, the farmers’ net income will be decreased to 50,2% for drip irrigation using gasoline and 27,9% for using electrical pumping energy. Moreover, 77,6% of the total cost is attributed to install the drip irrigation system which considered too expensive for the farmers, consequently the subsidy is still required. These results are useful to determine appropriate policy options such as subsidy, charge, tax and incentive to water use.